The impact of leadership components on turnover intent : the case of nurses - Batista, Maria da Graça Câmara (2019)
This study aimed to identify nurses’ leadership behavior in management functions and determine if leadership has a direct impact on turnover intention or career abandonment. This descriptive and inferential study was conducted in two public hospitals. Head nurses and nurses in general and specialist health care were invited to participate, except those working in operating or clinical services. The final sample consisted of 266 individuals (22 head nurses and 244 staff nurses) that responded to a questionnaire, which was organized into three distinct sections: (1) sample characterization; (2) the Leadership Effectiveness and Adaptability Description (LEAD), which was used to determine the situational leadership components; and (3) four closed questions relating to different turnover intentions. Data was collected in May 2009. The most expressive leadership styles are the S2 (persuading) and S3 (sharing) in both groups. In terms of turnover, the results showed strong positive associations with profile S2-S3 and with effective adaptability. Leaders’ with S2- S3 profiles easily delegate tasks and enhance the functional and emotional development of their collaborators. Effective adaptabilities requires that chief nurses tailor their leadership style to the situation and environment they are working, allowing that their actions meet the expectations of their subordinates. These two dimensions contribute positively to nurses’ retention.